Effect of an Antiracism Intervention on Racial Disparities in Time to Lung Cancer Surgery. Issue 16 (1st June 2022) - Charlot, Marjory; Stein, Jacob Newton; Damone, Emily; Wood, Isabella; Forster, Moriah; Baker, Stephanie; Emerson, Marc; Samuel-Ryals, Cleo; Yongue, Christina; Eng, Eugenia; Manning, Matthew; Deal, Allison; et al.
Abstract : PURPOSE: Timely lung cancer surgery is a metric of high-quality cancer care and improves survival for early-stage non–small-cell lung cancer. Historically, Black patients experience longer delays to surgery than White patients and have lower survival rates. Antiracism interventions have shown benefits in reducing racial disparities in lung cancer treatment. METHODS: We conducted a secondary analysis of Accountability for Cancer Care through Undoing Racism and Equity, an antiracism prospective pragmatic trial, at five cancer centers to assess the impact on overall timeliness of lung cancer surgery and racial disparities in timely surgery. The intervention consisted of (1) a real-time warning system to identify unmet care milestones, (2) race-specific feedback on lung cancer treatment rates, and (3) patient navigation. The primary outcome was surgery within 8 weeks of diagnosis. Risk ratios (RRs) and 95% CIs were estimated using log-binomial regression and adjusted for clinical and demographic factors. RESULTS: A total of 2, 363 patients with stage I and II non–small-cell lung cancer were included in the analyses: intervention (n = 263), retrospective control (n = 1, 798), and concurrent control (n = 302). 87.1% of Black patients and 85.4% of White patients in the intervention group ( P = .13) received surgery within 8 weeks of diagnosis compared with 58.7% of Black patients and 75.0% of White patients in the retrospective group ( P < .01) and 64.9% of Black patients and 73.2% of White patients ( P = .29) in the concurrent group. Black patients in the intervention group were more likely to receive timely surgery than Black patients in the retrospective group (RR 1.43; 95% CI, 1.26 to 1.64). White patients in the intervention group also had timelier surgery than White patients in the retrospective group (RR 1.10; 95% CI, 1.02 to 1.18). CONCLUSION: Accountability for Cancer Care through Undoing Racism and Equity is associated with timelier lung cancer surgery and reduction of the racial gap in timely surgery. Abstract :